Enhanced edge detection based on spin hall effect in the uniaxial crystal - Ji, Yan Wei; Ma, Xi Kui; Hu, Hua Jie; Li, Xin Zhong (Frontiers in Physics, 2022)
Optical analogue computing and spatial differentiation have received great attention in many fields. In the field of biology and medicine, it’s important to get the high contrast of images of subwavelength scale. Compared with other methods, the optical methods based on photonic spin hall effect (PSHE) have the advantages of low costs and detailed detections. But this method also has the disadvantages of lower contrasts. Our work is aimed to improve the contrasts for the edges. In the paper, we explore the spin hall effect of light (SHEL) based on uniaxial crystals and investigate the effects of these crystals on spatial differentiation. It can be seen that the spatial differentiation effects are consistent with the enhancement of PSHE. By comparing the spatial differentiation effects with that based on the traditional prism, it’s found that uniaxial crystal of certain dispersion relation could have a more significant effect on edge detections, which implies that this kind of medium would provide more possibilities in micro imaging.